2012
DOI: 10.1111/j.1365-2516.2012.02904.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of physical activity in children with haemophilia

Abstract: Summary The current widespread use of prophylaxis in developed countries has enabled greater participation in physical activity. However, there are no data available on leisure‐time physical activity in Australian children with haemophilia. The data reported here were obtained from a case‐crossover study nested in a prospective cohort study of 104 boys with moderate and severe haemophilia followed for one year. Each child's physical activity was assessed using a modifiable physical activity questionnaire (Kris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 27 publications
0
53
0
Order By: Relevance
“…The reduced number of significant variables (6 of 16) can be explained by the low scores obtained in HJHS in knees [0.45 (0.87) points] and ankles [0.42 (0.55) points], as well as by the fact that in 31.6% of children, the score was 0 points in knees and ankles. Today, thanks to the prophylactic treatment from an early age, children with haemophilia suffer few episodes of musculoskeletal bleeding and are physically active , being able to participate in one or more sports, making them as physically active as their peers . In our study, both groups performed the two mandatory weekly sessions of physical education at school.…”
Section: Discussionmentioning
confidence: 93%
“…The reduced number of significant variables (6 of 16) can be explained by the low scores obtained in HJHS in knees [0.45 (0.87) points] and ankles [0.42 (0.55) points], as well as by the fact that in 31.6% of children, the score was 0 points in knees and ankles. Today, thanks to the prophylactic treatment from an early age, children with haemophilia suffer few episodes of musculoskeletal bleeding and are physically active , being able to participate in one or more sports, making them as physically active as their peers . In our study, both groups performed the two mandatory weekly sessions of physical education at school.…”
Section: Discussionmentioning
confidence: 93%
“…12 Caregivers were also asked to indicate whether they preferred emicizumab prophylaxis over the patient's previous haemophilia treatment after the first 16 weeks of treatment; caregivers who preferred emicizumab were asked to select influencing factors and the top three factors in order of perceived importance (EmiPref survey 8 ). The types of activities were classified into three categories reflecting the risk of acute injury or collision (low, middle and high) that children could experience while participating in the activity.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…With the increased sports participation in PWH, sports participation and physical activity (PA) seem to have become relevant outcome parameters for PWH. However, most studies assessing sports participation in PWH showed conflicting results and reported on children and adolescents only …”
Section: Introductionmentioning
confidence: 99%